2022
DOI: 10.1111/jgh.15769
|View full text |Cite
|
Sign up to set email alerts
|

Depth of the cutting plane with underwater and conventional endoscopic mucosal resection: Post‐hoc analysis of a randomized study

Abstract: Background and Aim:A multicenter randomized controlled trial reported a better R0 resection rate for intermediate-sized (10-20 mm) colorectal polyps with underwater endoscopic mucosal resection (UEMR) than conventional endoscopic mucosal resection (CEMR). To clarify whether UEMR removes enough submucosal tissue in the removal of unpredictable invasive cancers, we investigated the cutting plane depth with UEMR versus CEMR. Methods: This was a post-hoc analysis of a randomized controlled trial in which 210 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In our current strategy, we combined new-generation polypectomy for colorectal polyps, including cold polypectomy and UEMR, which have been reported previously 8 9 26 27 28 . While CSP has a shallow cutting plane and can leave dysplastic tissue in situ when it removes lesions invading deeper than the muscularis mucosa 12 , the cutting plane of UEMR is reportedly as deep as conventional EMR 29 30 . Conversely, CSP reportedly has a low risk of adverse events 16 ; however, UEMR involves the risk of perforation and delayed hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current strategy, we combined new-generation polypectomy for colorectal polyps, including cold polypectomy and UEMR, which have been reported previously 8 9 26 27 28 . While CSP has a shallow cutting plane and can leave dysplastic tissue in situ when it removes lesions invading deeper than the muscularis mucosa 12 , the cutting plane of UEMR is reportedly as deep as conventional EMR 29 30 . Conversely, CSP reportedly has a low risk of adverse events 16 ; however, UEMR involves the risk of perforation and delayed hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…removes lesions invading deeper than the muscularis mucosa [12], the cutting plane of UEMR is reportedly as deep as conventional EMR [29,30]. Conversely, CSP reportedly has a low risk of adverse events [16]; however, UEMR involves the risk of perforation and delayed hemorrhage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The results of a multicenter randomized controlled trial indicated that UEMR, with a cutting plane depth comparable to that of CEMR, which can adequately resect the submucosal layer and is a feasible alternative for the histopathological evaluation of unpredictable submucosal invasive tumors[ 16 ].…”
Section: Uemrmentioning
confidence: 99%
“…Underwater EMR was first reported by Binmoeller et al in 2012 [1], and we reported its usefulness for resecting colorectal polyps [2] and duodenal tumors. The cutting depth with underwater EMR was comparable to that of conventional EMR [3]. For cases in which pathological diagnosis is difficult by endoscopic biopsy because only nontumor epithelium is obtained, endoscopic ultrasonographyguided fine-needle aspiration may be performed [4]; however, this procedure ▶ Fig.…”
mentioning
confidence: 97%